TRADISI PENDISTRIBUSIAN ZAKAT FITRAH KEPADA USTAZ DI DESA BATONAONG - Siti Khoiriyah (Maliyah : Jurnal Hukum Bisnis Islam, 2016)
The tradition of distributing zakat fitrah to ustadh have been carried out for generations in Batonaong Arosbaya Bangkalan Madura, the implementation prefers ustadh as the recipients of the other asnaf, although classified able. As for the distribution of zakat fitrah done by muzakki a direct way to the homes of teachers or religious leaders around their villages. The tradition of zakat distribution in the model does not comply with Islamic law on the grounds: First, the contradiction with an explanation of Surah at-Tawbah verse 60 in Tafsir Ahkam which states that the distribution of zakat must be equitable in the sense not only on one asnaf; second, the contradiction with the main purpose of zakat which provide help for poor people and those who desperately need help and to lead a noble life situation during idul fitri.